Micro hydro power plant for self generated electricity / Syahirah Saidi - Saidi, Syahirah (2018)
Malaysia in its efforts to sustain energy which acts as the main pillar of sustainable development. More attention needs to be paid toward the development of renewable energy, green technology and energy conservation in the future. Therefore, renewable power generation has been implemented which is hydro power to support energy efficiency. However, current studies show that the pattern of power generation in Malaysia is only on a large scale project. Thus, a desk study will be conducted by providing a review of relevant research which concentrates on the concept of Micro hydro power plant to fulfill the high demand of electrical energy. It will also identify problems andthe impact of non-renewable energy on the environment, and propose its potential for off grid power demand. A new approach of Micro Hydro power plant can support energy efficiency as it provides both an efficient and a reliable form clean source of renewable energy. The Micro Hydro power plant concept requires a little or no reservoir to power the turbine. This small scale alternative electrical power production can meet sustainable energy needs which can be used in a flexible area, location and environment.